IMAN DI TENGAH KETAKUTAN : Berdasarkan Analisa Eksistensial atas Angin ribut diredahkan (Mrk. 4: 35-41) - Laurensius tonny Kuntag; Antonius Tukiran (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This paper analyzes the passage of Mark 4:35–41 (Jesus Calming the Storm) using narrative hermeneutics, socio-historical analysis, and Wirkungsgeschichte(reception history) to uncover the dynamics of faith and fear within the human experience. This pericope is understood not merely as a report of a nature miracle, but as a theological narrative intentionally constructed by Mark to shape the faith of the disciples and the reader’s community amidst crisis. The textual-narrative analysis reveals a structural movement from stillness to chaos and back to silence, mirroring the existential dynamics of humans when faith is tested by tangible threats. The disciples' fear is characterized as not only emotional but primarily relational and existential—a crisis of trust regarding the perceived indifference of a